2013
DOI: 10.1016/j.jaip.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy and Increased Asthma Morbidity in a School-Based Inner-City Asthma Study

Abstract: Background Children with asthma have increased prevalence of food allergies. The relationship between food allergy and asthma morbidity is unclear. Objective We aimed to investigate the presence of food allergy as an independent risk factor for increased asthma morbidity using the School Inner-City Asthma (SICAS), a prospective study evaluating risk factors and asthma morbidity among urban children. Methods We prospectively surveyed 300 children from inner-city schools with physician-diagnosed asthma, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 28 publications
5
39
2
7
Order By: Relevance
“…The prevalence of self-reported food allergies in our adolescent sample was 30%, a rate slightly higher than that of a previous report in younger children with asthma, 24% [10]. However, our food allergy rate is considerably higher than the prevalence of self-reported food sensitization, 17%, in the general population based on a large U.S. national survey [11].…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of self-reported food allergies in our adolescent sample was 30%, a rate slightly higher than that of a previous report in younger children with asthma, 24% [10]. However, our food allergy rate is considerably higher than the prevalence of self-reported food sensitization, 17%, in the general population based on a large U.S. national survey [11].…”
Section: Discussioncontrasting
confidence: 79%
“…(6) Prior studies have identified an association between IgE-mediated food allergy and the development of comorbid atopic conditions including asthma and allergic rhinitis. (7, 8) However, the extent to which IgE-mediated food allergy is associated with eosinophilic esophagitis (EoE) is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…(13) In particular, sensitization to multiple allergens and having a food allergy are risk factors for severe asthma exacerbations and death. (11, 16, 17)…”
Section: Introductionmentioning
confidence: 99%